2019
DOI: 10.1007/978-3-030-35151-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Structured Approach to Converging Business Process Management and Customer Experience Management Initiatives

Abstract: Both in theory and practice, a lack of a formulated structure to facilitate integrated modeling and analysis of internal business processes and customer experiences external to the organization has been identified by many authors. Tackling this issue, a convergent approach aligning Business Process Management (BPM) and Customer eXperience Management (CXM) initiatives, is proposed in the paper, along with a full set of top-down BPM-CXM models varying in the level of detail. To validate the proposed models, a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Specifically (ibid, p. 23): (i) process identification, (ii) process discovery (also called as-is process modelling), (iii) process analysis, (iv) process redesign (also called process improvement), (v) process implementation, and (vi) process monitoring thus become (i) process and customer experience identification (resulting in process and customer experience architecture), (ii) process and customer experience discovery (including as-is process modelling and as-is customer journey mapping), (iii) process and customer experience analysis (resulting in insights from both perspectives), (iv) process and customer experience redesign (resulting in improvements reflected in to-be process models and to-be customer journey maps), (v) process implementation, and (vi) process and customer experience monitoring and control. In 2019 and 2020, the convergence concept has been endorsed and evaluated with experts, and a set of guidelines have been proposed to demonstrate and operationalise it (Pavlić & Ćukušić, 2019b).…”
Section: Methodology For Convergent Bpm and Cxmmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically (ibid, p. 23): (i) process identification, (ii) process discovery (also called as-is process modelling), (iii) process analysis, (iv) process redesign (also called process improvement), (v) process implementation, and (vi) process monitoring thus become (i) process and customer experience identification (resulting in process and customer experience architecture), (ii) process and customer experience discovery (including as-is process modelling and as-is customer journey mapping), (iii) process and customer experience analysis (resulting in insights from both perspectives), (iv) process and customer experience redesign (resulting in improvements reflected in to-be process models and to-be customer journey maps), (v) process implementation, and (vi) process and customer experience monitoring and control. In 2019 and 2020, the convergence concept has been endorsed and evaluated with experts, and a set of guidelines have been proposed to demonstrate and operationalise it (Pavlić & Ćukušić, 2019b).…”
Section: Methodology For Convergent Bpm and Cxmmentioning
confidence: 99%
“…Customer eXperience (CX). The prospects and implications of business process analysis and optimisation when using the BPM-CX convergent approach, in comparison with the traditional BPM approach, have been presented elsewhere (Pavlić & Ćukušić, 2019a, Pavlić & Ćukušić, 2019b.…”
Section: New Research Directions In the Field Of Digital Transformation: Bpm And CX Convergencementioning
confidence: 99%
See 1 more Smart Citation
“…Bernardo Junior and de Padua (2023) point out that BPM must enable fast and flexible process changes while providing a better CX. While analysing the current state of alignment of BPM and CXM, Pavlić and Ćukušić (2019) found that BPM initiatives in practice are often not focused on enabling better CX. They also suggested the alignment of BPM and CXM initiatives in the form of an integrated BPM-CXM lifecycle that upgrades the traditional BPM lifecycle (Dumas et al.…”
Section: Theoretical Background and Research Modelmentioning
confidence: 99%
“…Practical implications The study's findings enable organisations to guide the development of BPM capabilities so that BPM can play an important role in building a customer-centric organisation. Both initiatives, BPM and CXM, must therefore work in unison (Moore and Misiak, 2018;Pavli c and Cuku si c, 2019) to develop a decision-making culture based on facts and agility in process improvements. In summary, understanding the importance of and developing various new and enhanced BPM capabilities permits organisations to dynamically capture ever-changing customer needs and expectations, to transform their business processes with the customer perspective in mind, and manage their business operations to improve competitiveness and business performance.…”
Section: Bpmj 308mentioning
confidence: 99%